PENGARUH LENDING DAN FUNDING TERHADAP LOAN TO DEPOSIT RATIO PADA BANK PERKREDITAN RAKYAT DANA NUSANTARA - Efriyenty, Dian (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The Bank is a financial institution whose activities to collect funds from the public and distribute in the form of credit. This study aimed to determine the effect of a given Lending and Funding of the Loan to Deposit Ratio (LDR) to the Fund RB archipelago. The population in this study consisted of 27 Rural Bank registered with the Financial Services Authority and Bank Indonesia. The sample used in this study only one Rural Bank is BPR Dana archipelago. The data used in this research are secondary data from the financial statements of the period June 2009 to June 2018. Methods of data analysis using multiple linear regression and tested using SPSS version 20 program.Simultaneous research results (Test F) showed significant effect, which means lending and funding together give a significant effect on the loan to deposit ratio so the regression model included in this study feasible to study. Partially through the t test result is the variable lending significant effect on the loan to deposit ratio, while the variable funding does not significantly affect the loan to deposit ratio.